Evaluasi Pengembangan Pembelajaran Tahfidz Dengan Metode Talaqqi Dan Audio Visual Pada Anak Usia Dini - Listiani, Dwi; Ridho, Achmad Rasyid (Indonesian Journal of Islamic Educational Review, 2024)
Overall, the talaqqi and audio visual methods have proven effective in improving the tahfidz abilities of early childhood at Markaz Alkautsar Magelang, although there are several aspects that need to be improved to achieve more optimal results. This research aims to evaluate the development of tahfidz learning using talaqqi and audio-visual methods in early childhood at Markaz Alkautsar Magelang. The research method used is a combination of observation, interviews, questionnaires and memorization tests to collect data from teachers, parents and children. Aspects evaluated include effectiveness, efficiency, relevance and impact of learning methods on children's tahfidz development. The results showed that the talaqqi and audio-visual methods significantly improved children's memorization abilities. Observations and interviews with teachers revealed that this method was able to increase children's involvement and motivation in learning the Koran. Parents also reported positive improvements in their children's memorization abilities. Analysis of data from the memorization test shows a significant increase between the pre-test and post-test results. However, this research also found several challenges, such as technical difficulties in using audio-visual devices and the need for further training for teachers to maximize the use of these methods. Based on these findings, it is recommended to conduct continuous training for teachers and improve the technological infrastructure at Markaz Alkautsar